Social stratification of the Jewish population of Roman Palestine in the period of the Mishnah, 70-250 CE - Rozenfeld, Ben Tsiyon (The Brill reference library of ancient Judaism, 2020)
This book defines, uncovers, dissects, and arranges the economic groups in Roman Palestine in the first centuries CE. It shows that, alongside the rich and poor, there were significant middling groups that constituted the backbone of Jewish society.